SOME CHARACTERISTICS OF READING AS A TYPE OF SPEECH ACTIVITY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Reading is indeed a fundamental aspect of cognition and communication in both personal and professional life. It not only enhances knowledge but also fosters understanding, empathy, and personal growth. Reading in a foreign language, in particular, accelerates information acquisition and is crucial for language learning and practical usage.